PENGARUH ENDORPHIN MASSAGE TERHADAP PENGELUARAN ASI PADA IBU POST PARTUM - Magfirah Magfirah; Idwar Idwar (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: Decreased levels of endorphins and oxytocin are known to be one of the factors causing breast milk production problems in the first days after birth. Low levels of these hormones are also an obstacle in exclusive breastfeeding. Endorphin Massage can provide a feeling of calm and comfort during lactation, thereby increasing the response of the posterior pituitary to producing the hormone oxytocin to increase let down reflex.Research Objectives: to determine the effect of Endorphin Massage on Breastfeeding Expenditures in Post Partum Mothers in the Work Area of Langsa Lama Public Health Center, Langsa City.Methods: This type of research is a quasi experiment, with a post test only control group design approach. The number of samples of 20 respondents, divided into 2 groups (Endorphin Massage and control) each of 10 respondents.Results: The results of the independent T test showed that the mean value of the Endorphin Massage treatment group was 8.50 and the control group was 4.90 (0.000) with p <0.05. The results of this study indicated an increase in milk production in the group that received the Endorphin Massage compared to the control group.Conclusions There is an effect of the Endorphin Massage method on breastfeeding in post partum motherssuggestions: . It is hoped that health workers can apply the Endorphin Massage method to post partum mothers in an effort to increase milk production. Keywords: Endorphin Massage, Breast Milk Production ABSTRAK Latar Belakang: Penurunan kadar endorfin dan oksitosin diketahui sebagai salah satu faktor penyebab masalah produksi ASI pada hari-hari pertama setelah bayi lahir. Rendahnya kadar hormon tersebut juga menjadi kendala dalam pemberian ASI Eksklusif. Endorphin Massage dapat memberikan rasa tenang dan nyaman selama masa laktasi sehingga meningkatkan respon hipofisis posterior untuk memproduksi hormon oksitosin dalam meningkatkan let down reflex.Tujuan Penelitian: diketahui Pengaruh Endorphin Massage Terhadap Pengeluaran ASI Pada Ibu Post Partum Di Wilayah Kerja Puskesmas Langsa Lama Kota Langsa.Metode Penelitian: Jenis penelitian quasi experiment, dengan pendekatan post test only control group design. Jumlah sampel 20 responden, dibagi menjadi 2 kelompok (Endorphin Massage dan kontrol) masing-masing 10 responden.Hasil Penelitian: Hasil uji independen T test didapatkan nilai rerata kelompok perlakuan Endorphin Massage sebesar 8,50 dan kelompok kontrol 4,90 (0,000) dengan p < 0,05. Hasil penelitian ini menunjukkan adanya peningkatan produksi ASI pada kelompok yang mendapatkan Endorphin Massage dibandingkan kelompok kontrol.Kesimpulan: Terdapat pengaruh metode Endorphin Massage terhadap pengeluaran ASI pada ibu post partumSaran diharapkan kepada petugas kesehatan agar dapat menerapkan metode Endorphin Massage kepada ibu post partum dalam upaya meningkatkan produksi ASI. Kata Kunci: Endorphin Massage,Pengeluaran ASI